La « femme·eux·ze » musique québécoise : La recherche sur les genres, les sexualités et autres pratiques non dominantes en musique au Québec (1874-2022) - Blais-Tremblay, Vanessa (Centre de recherche interuniversitaire sur la littérature et la culture au Québec [CRILCQ], 2023)
C’est là un ouvrage de référence qui présente la recherche sur la musique, les genres et les sexualités, et plus largement la vie musicale non dominante au Québec depuis le dernier quart du XIXe siècle jusqu’à aujourd’hui. Issu des travaux réalisés en 202-2022 par le pôle universitaire DIG! Différences et inégalités de genre dans la musique au Québec (D!G), un réseau interdisciplinaire et intersectoriel qui réunit les chercheur·ses, publics, artistes et autres professionnel·les de la musique qui s’intéressent à cette thématique, l’ouvrage comprend une revue de la littérature et une bibliographie de plus de 800 ressources scientifiques.

Les femmes dans l’industrie musicale canadienne francophone - Bissonnette, Joëlle (Fondation Musicaction, 2022)

Barbara Scales - Farnsworth, Brandon; Massera, Vanessa (Taking the Temperature: Crisis, Curating, and Musical Diversity, 2021)

Empowering Diversity: A Study Connecting Women in Leadership to Company Performance in the Canadian Music Industry - Women In Music Canada (Women In Music Canada, 2019)
Gender diversity in the music industry is low, both in Canada and internationally. The lack of diversity may represent a competitive disadvantage, as diversity is known to promote innovation and broad thinking, which is precisely what the music industry needs as it undergoes rapid change. This study, performed by Women in Music Canada in collaboration with PwC, assesses the impact of gender diversity of leadership within the Canadian music industry and the impact on company performance.

Aller à la quête de l’œuvre : Véronique Lacroix et les 30 ans de l’ECM+ - Champagne, Éric (Circuit : musiques contemporaines, 2018)
Publisher: Circuit, musiques contemporaines

Parcours dans la programmation des concerts du Nouvel Ensemble Moderne - Couture, Ariane (Circuit : musiques contemporaines, 2013)
During its 25 years of activities, the nem has played 635 works by 374 composers at local concerts, public workshops or world tours. Collectively, these works cover most of the aesthetic tendencies of the music of the 20th century. However, it is possible to define the repertoire of the ensemble along two main axes: on one hand, works that have become “classics” of contemporary music, and, on the other hand, new works engaged in musical innovation. Thus, the policy for disseminating works through concerts established by Lorraine Vaillancourt introduces a new culture within the world of musical creation, based on the development of a repertoire of works from the 20th and 21st centuries.
Publisher: Les Presses de l’Université de Montréal
Keywords: Nouvel Ensemble Moderne; concert; musical programming; programmation musicale; repertoire; répertoire

« Donner le temps » : entretien avec Lorraine Vaillancourt - Goldman, Jonathan (Circuit : musiques contemporaines, 2013)
In an interview with Lorraine Vaillancourt, the founder and artistic director of the Nouvel Ensemble Moderne (nem) recounts her musical education in Quebec, Montreal and Paris, and goes on to describe the establishment and development of her ensemble, the choice of repertoire and her plans for the future.
Publisher: Les Presses de l’Université de Montréal
Keywords: Lorraine Vaillancourt; Nouvel Ensemble Moderne; contemporary music ensemble; direction musicale; ensemble de musique contemporaine; musical conducting

Gender, Genre and Electroacoustic Soundmaking Practices - McCartney, Andra (Intersections: Canadian Journal of Music / Intersections : revue canadienne de musique, 2006)
This article is an exploration of how genres and practices of electroacoustic soundmaking are gendered, examining processes of gendering in language used in the early dichotomous categorization between musique concrète and elektronische Musik, then thinking about related arguments concerning abstraction, context, and compositional control in the writings of electroacoustic soundmakers including Pierre Schaeffer, Pierre Boulez, Daphne Oram, Pauline Oliveros, and several participants of the In and Out of the Sound Studio project. Analysis of their practices and ideas suggests different ways of conceptualising electroacoustic genres, their related practices, and roles of contemporary electroacoustic soundmakers (composers, artists, producers, mixers, audiences...), by examining the potentials of the concepts of empathetic knowledge and ecological thinking advanced by feminist epistemologist Lorraine Code.

La alegría de hacer música contemporánea: entrevista con Lorraine Vaillancourt [La joie de faire de la musique contemporaine : entretien avec Lorraine Vaillancourt] - Stan, Luana (Doce notas preliminares, 2006)
Publisher: Doce notas Section: Doce notas preliminares: revista de música y arte

Diane Leboeuf: from mixing boards to museums - Gasior, Lisa; McCartney, Andra (Musicworks, 2004)